SUSTAINABLE FOREST MANAGEMENT: A SOCIAL CAPITAL APPROACH FOR WOMEN FOREST FARMERS ON THE SLOPES OF MOUNT KENDENG NORTH, CENTRAL JAVA - Raden Roro Ilma Kusuma Wardani; Widiyanto Widiyanto; Ismi Dwi Astuti Nurhaeni; Andayani Listyawati (GeoEco, 2024)
The social capital approach and collaboration are the main focus in the management of natural resources such as forests. The social capital owned by women forest farmers is realized through social leadership, local wisdom, trust, and social institutions. This research aims to map social capital in ecological, social, and economic aspects of forest conservation efforts. The research was conducted on women forest farmers on the slopes of Mount Kendeng Utara, Central Java, namely in Blora Regency and Rembang Regency. Data were collected through moderate participation observation and in-depth interviews with several informants, then analyzed using qualitative methods of case studies. The typologies of social capital found are divided into three: bonding, bridging, and linking. In sustainable forest management, the dominant social capital in the economic aspect is bonding social capital, which increases the motivation, solidarity, productivity, and income diversification of women forest farmers. Bridging social capital strengthens social and ecological sustainability through compliance with the chairman of the Forest Farmers Group who are indigenous leaders, facilitating the exchange of information and forest management practices. Strengthening the social capital of women forest farmers requires a participatory, equitable, and gender-just approach to achieve sustainable forest management.